Inventory of pests attacking Adenium spp. in Denpasar city - Gargita, I Wayan Diksa; Sudiarta, I Putu; Yuliadhi, Ketut Ayu; Sumartayasa, I Wayan Andi (Universitas Trunojoyo Madura, 2024)
The cultivation of Adenium spp. encountered several challenges involving physical, environmental, and plant pest interference factors. Inventory of pests aimed to find out the kind of pests, the symptoms of the attacks, and the percentage of the pests that attack Adenium spp. Samples were taken using a purposive method by taking pictures and observing plants attacked by pests in 4 sub-districts in Denpasar, namely West Denpasar, East Denpasar, South Denpasar, and North Denpasar. The research results show that several pests attack Adenium spp. in Denpasar City, including mealybugs, spider mite, red cotton bug, and aphids. The study's findings indicate that Adenium spp. in Denpasar City are susceptible to several pests, such as mealybugs, spider mite, red cotton bug, and aphids. These organisms induce the dehydration, withering, and stunted growth of plants due to fluid loss. Mealybugs exhibit the highest incidence of infestation, with a prevalence rate of 85%. Spider mites follow with an infestation rate of 50%, while red cotton bug and aphids display infestation rates below 50%. The presence of several pest insects in Adenium spp. is indicative, with certain pests posing a significant threat to the plants, perhaps resulting in severe damage or even plant mortality. This research can provide additional information of pests that attack ornamental plants so that the strategy of pest control on ornamental plants, especially Adenium, can be developed.